Edukasi Pemanfaatan Lahan Pekarangan Budidaya Tanaman Sayuran Dengan Sistem Irigasi Sederhana Pada Masyarakat Desa Suco Jember - Annisa Lutfi Alwi; Sepdian Luri Asmono; Ujang Setyoko; Rudi Wardana; Zora Olivia; Trisnani Alif (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2025)
This community service program focuses on helping the people of Suco Village, Jember, particularly PKK mothers and youth, utilize their yards for vegetable cultivation. The main challenges include limited land, water scarcity, and a lack of cultivation knowledge. To address these issues, the program offers counseling, demonstrations, and hands-on practice in vertical cultivation and simple drip irrigation. Participants have increased their understanding of these techniques and can now design and install irrigation systems independently. This technology improves water efficiency and enables effective plant growth in small spaces. The initiative not only enhances household food independence and raises awareness of healthy vegetables but also encourages cooperation and productive economic opportunities. Overall, this education on vertical cultivation serves as an effective community empowerment strategy that contributes to family food security.